Kenya Climate Change Project dataset - Adam, Rahma (2024)
The datasets contain quantitative and qualitative data used to assess the gendered perception of climate change impacts and livelihood vulnerability among fishing populations in Lake Victoria region (Homabay and Migori counties), Kenya.